Lived experiences of supporting the community engagement mandate of a rural-based university in South Africa - Nemadodzi, N.; Nevhudoli, N.D. (South African Journal of Higher Education, 2025)
In this article, lived experiences of coordinating the community engagement mandate in a rural-based university of South Africa were explored from a personal experiential perspectives. This article explored experiences regarding the involvement regarding coordination of different projects within a rural community-based University, University of Venda. A Qualitative methodology, using an interpretivist paradigm were followed given the type of this article. The article documented a lived experiences of being within the directorate of Community engagement. The researchers has revealed multiple interpretations of the lived experiences as an Community Engagement Manager and Administrative Officer at the CE Directorate . Researchers also used narrative analysis and construct from their own personal experiences, that means there was a dual layer of interpretation of narrative analysis of their own lives. The shared positive and negative experiences were taken from the engagement with students, academics, NGOs/NPOs, government departments, municipalities, and grassroots communities. Reflections of the researchers will (a) contribute to the understanding of the terrain of coordinating community engagement in rural-based universities in South Africa; (b) identify best practices; and (c) provide recommendations for universities to improve their community engagement enterprise. Experiences contained in this article rarely find space in academic discourse. The invasion of researchers in the academic space might help reshape conference conversations, thereby opening other pathways of understanding community engagement especially in historically disadvantaged universities. There is also a need for further research on related aspects of the community’s involvement.